The dispersal of protoplanetary discs. Issue 5 (June 2014) - Ercolano, B.
Abstract Protoplanetary discs are a natural consequence of the star formation process and as such are ubiquitous around low‐mass stars. They are fundamental to planet formation as they hold the reservoir of material from which planets form. Their evolution and final dispersal and the timescales that regulate these process are therefore of particular interest. In this contribution I will review the observational evidence for the dispersal of discs being dominated by two timescales and for the final dispersal to occur quickly and from the inside out. I will discuss the current theoretical models, including X‐ray photoevaporation, showing that the latter provides a natural explanation to the observed behaviour and review supporting and contrasting evidence. I will finally introduce a new mechanism based on the interaction between planet formation and photoevaporation that may explain a particular class of transition discs with large inner holes and high accretion rates that are problematic for photoevaporation models and planet formation models alone. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)